2019
DOI: 10.1016/j.jarmac.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Nonbelieved memories in the false memory archive.

Abstract: We dedicate the current work to Alan Scoboria, a brilliant memory researcher and dear friend, who passed away too soon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(57 reference statements)
4
11
0
Order By: Relevance
“…Follow-up studies have shown similar results (Brédart & Bouffier, 2016; Vanootighem et al, 2019). For example, Otgaar et al (2020) examined the memory reports from the False Memory Archive, an art website collecting experiences of false memories from the general population (https://www.falsememoryarchive.com/), and found that a large proportion ( n = 208, 41.6%) of reports could be classified as NBMs (i.e., fitting in with the high recollection and low belief in occurrence pattern). More importantly, these NBM reports contained similar reasons for why belief was reduced as in previous studies.…”
Section: Prevalence Of Nbm and Reasons For Belief Reductionmentioning
confidence: 99%
“…Follow-up studies have shown similar results (Brédart & Bouffier, 2016; Vanootighem et al, 2019). For example, Otgaar et al (2020) examined the memory reports from the False Memory Archive, an art website collecting experiences of false memories from the general population (https://www.falsememoryarchive.com/), and found that a large proportion ( n = 208, 41.6%) of reports could be classified as NBMs (i.e., fitting in with the high recollection and low belief in occurrence pattern). More importantly, these NBM reports contained similar reasons for why belief was reduced as in previous studies.…”
Section: Prevalence Of Nbm and Reasons For Belief Reductionmentioning
confidence: 99%
“…Nonbelieved memories (NBMs) are memories that were once believed to genuinely reflect past occurrences, but the rememberer decided to reduce or completely relinquish belief in occurrence for the event. Reduced belief in occurrence frequently emerges after obtaining some form of disconfirming information regarding the occurrence of the event in the memory (Otgaar et al, 2019; Scoboria, Mazzoni, & Boucher, 2017). Despite the reduction in belief in the event's occurrence, NBMs continue to be experienced as “memory‐like” and retain vivid recollective features, including visual and spatial detail, and are accompanied by autonoetic awareness and feelings associated with re‐experiencing the past (Mazzoni et al, 2010; Otgaar, Scoboria, & Mazzoni, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Highlights that particularly strike me include studies of "disowned" memories (essentially accurate memories that a person comes to believe are false) (Mazzoni, Scoboria, & Harvey, 2010). An analysis of nonbelieved autobiographical memories collected as part of an art project (Otgaar et al 2019;cf. Ost, 2017).…”
Section: Big Picturementioning
confidence: 99%